Working between systems: an umbrella review of care navigator roles and responsibilities - Wijekulasuriya, Shalini; Wahlstrom, Leanne; Lewis, Suzanne; Triandafilidis, Zoi; Rojas, Christina; Goodwin, Nicholas; Semkina, Antonina; Boaz, Annette; Norrie, Caroline; Zurynski, Yvonne (Frontiers in Health Services, 2025)
BackgroundA growing workforce is being employed internationally to assist patients in navigating between health and social care providers. These roles operate under various care models including patient navigation, social prescribing, and care coordination; tasks and responsibilities of care navigators are highly variable and often lack clarity. Understanding the similarities and differences amongst care navigator roles could improve the embedding of roles into health and social care systems and legitimise professional identity. This umbrella review synthesises evidence on care navigator roles, role titles, tasks, and functions, across diverse models that integrate care at the health and social care interface.MethodsMEDLINE, Embase, CINAHL, Scopus, and PsycINFO were searched from 1 Jan 2019–31 May 2024. Reviews that used systematic, scoping, or other rigorous methodology were included if they discussed the role or function of workers who coordinated services involving health and social care. Data were synthesised using an inductive thematic approach.ResultsTwenty-six review articles were included, which synthesised 824 unique primary sources. Seventy-eight unique role titles were used to describe care navigators, which aggregated under seven role categories: Patient Navigator, Link Worker, Care Coordinator, Case Manager, Social Prescriber, Intermediary, Health Mediator. The most common were Patient Navigator and Link Worker. Tasks related to navigation, building service users' capacity for self-management, and providing person-centred care overlapped across all role categories, indicating the core functions of the navigation workforce. Patient Navigators' scope of practice included the provision of education, appointment coordination, and assistance with logistic issues, while the roles of Link Workers typically only provided referral-based navigation and developed the capacity of service users for self-management.ConclusionsThe range in the titles and role scope of care navigators highlights increasing demand for system integration, however, the high variability of interchangeable terms and overlapping tasks create complexity for service users, providers, and researchers. An international Delphi study could create a consensus on the nomenclature and taxonomy for navigator roles that interface between health and social care systems. Developing professional identities, training, and strategies to seamlessly embed such roles into existing health and social care structures is also needed.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO #CRD42024572605.